MRI-derived bound and pore water concentrations as predictors of fracture resistance - Manhard, Mary Kate; Uppuganti, Sasidhar; Granke, Mathilde; Gochberg, Daniel F.; Nyman, Jeffry S.; Does, Mark D. (Bone (New York, N.Y.), 2016)
Accurately predicting fracture risk in the clinic is challenging because the determinants are multi-factorial. A common approach to fracture risk assessment is to combine X-ray-based imaging methods such as dual-energy X-ray absorptiometry (DXA) with an online Fracture Risk Assessment Tool (FRAX) that includes additional risk factors such as age, family history, and prior fracture incidents. This approach still does not adequately diagnose many individuals at risk, especially those with certain diseases like type 2 diabetes. As such, this study investigated bound water and pore water concentrations (Cbw and Cpw) from ultra-short echo time (UTE) magnetic resonance imaging (MRI) as new predictors of fracture risk. Ex vivo cadaveric arms were imaged with UTE MRI as well as with DXA and high-resolution micro-computed tomography (μCT), and imaging measures were compared to both whole-bone structural and material properties as determined by three-point bending tests of the distal-third radius. While DXA-derived areal bone mineral density (aBMD) and μCT-derived volumetric BMD correlated well with structural strength, they moderately correlated with the estimate material strength with gender being a significant covariate for aBMD. MRI-derived measures of Cbw and Cpw had a similar predictive ability of material strength as aBMD but did so independently of gender. In addition, Cbw was the only imaging parameter to significantly correlate with toughness, the energy dissipated during fracture. Notably, the strength of the correlations with the material properties of bone tended to be higher when a larger endosteal region was used to determine Cbw and Cpw. These results indicate that MRI measures of Cbw and Cpw have the ability to probe bone material properties independent of bone structure or subject gender. In particular, toughness is a property of fracture resistance that is not explained by X-ray based methods. Thus, these MRI-derived measures of Cbw and Cpw in cortical bone have the potential to be useful in clinical populations for evaluating fracture risk, especially involving diseases that affect material properties of the bone beyond its strength. [Display omitted] •Bound and pore water concentration correlated similarly with BMD to strength.•Bound water concentration was the only parameter that correlated with toughness.•MRI measures have the ability to probe bone material properties.